2017
DOI: 10.1007/s00382-017-3555-7
|View full text |Cite
|
Sign up to set email alerts
|

Multi-model assessment of the impact of soil moisture initialization on mid-latitude summer predictability

Abstract: Land surface initial conditions have been recognized as a potential source of predictability in sub-seasonal to seasonal forecast systems, at least for near-surface air temperature prediction over the mid-latitude continents. Yet, few studies have systematically explored such an influence over a sufficient hindcast period and in a multi-model framework to produce a robust quantitative assessment. Here, a dedicated set of twin experiments has been carried out with boreal summer retrospective forecasts over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 69 publications
3
40
0
Order By: Relevance
“…Despite the very different nature of this SM database, it is worth noting that the identified hot spots bewteen the NHN and NHD and the ERA-Interim/Land SM dataset agree well with the previous results for NHD/NHN in the Balkans and Iberia in May, June and July. The NHD results are also in accordance with model-based studies investigating the role of SM initial conditions on temperature predictability (Prodhomme et al 2016, Ardilouze et al 2017 which identifies the Balkans hotspot for forecasts initialized in May and valid for June-July. However, those studies did not find any clear signal over Iberia, as our results suggest.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Despite the very different nature of this SM database, it is worth noting that the identified hot spots bewteen the NHN and NHD and the ERA-Interim/Land SM dataset agree well with the previous results for NHD/NHN in the Balkans and Iberia in May, June and July. The NHD results are also in accordance with model-based studies investigating the role of SM initial conditions on temperature predictability (Prodhomme et al 2016, Ardilouze et al 2017 which identifies the Balkans hotspot for forecasts initialized in May and valid for June-July. However, those studies did not find any clear signal over Iberia, as our results suggest.…”
Section: Discussionsupporting
confidence: 84%
“…These results are of high importance for climate modelers (Ardilouze et al 2017) and responsible authorities, as the occurrence of drought induced extreme temperatures, in particular heatwaves, can have costly impacts (Díaz et al 2006Sánchez-Benítez et al 2017. The hotspots in the BKS and northern Italy were previously identified and analyzed for SM-temperature feedbacks (Whan et al 2015, Ardilouze et al 2017.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that land surface properties such as soil moisture also influence heatwaves (e.g. Quesada et al 2012, Ardilouze et al 2017), and may therefore provide an important source of predictability for heatwaves. However, since our experiments require a coupled high-resolution prediction model, we decided to focus all our available computational resources on ocean, sea-ice and atmosphere initialisation only.…”
Section: Introductionmentioning
confidence: 99%
“…Having identified these characteristics of extreme temperature transitions, future research is necessary to determine the relationship between transitions and the ambient circulation features. For instance, understanding whether similar circulation features result in transitions in different regions of the country or during different times is necessary to ascribe a mechanism to the observed changes in extreme temperature variation and potentially explain the geographic patterns of change, which may be related large scale factors such as preferred wave patterns or local features such as regional soil moisture trends (e.g., Ardilouze et al, 2017).…”
Section: Discussionmentioning
confidence: 99%